(3cJGH GdLhGQM hYdhe GdHROQIs - (3GdbQTj, CHh HcQ Hf jhSa Hf CHj HcQ Hf MSf GdbGSej GdbQTj GdYdhjs ((3CMeO Hf GdMGL MSfs)
(3ChdgG (B:s
(3PcQhG GdKbGJ ef GdQhGI ef Cgd GdeYQaI Cf GdEScfOQ GdQhej bGd ddMceGA GdeNJdajf dNOeJg jheG(B: (3CQjO Cf JYpqQahG dj WHjYI GdHGRjs
(3BNQgG (B:s
(3BNQgG(B: (3hjNdW eYgG ef GdScQ GdWHQRO KdGKI CLRGA, aEPG YGO GdWjQ ef GdUjO ojOQL dg aj oWrYeg TjA efg aEfg jfaYg (B... (3hjYWi dg aj MGd aj GdTgQ eQJjf(B. (3Je GdcJGHs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdeYGQa GdYGeIs